PENGARUH KEPEMIMPINAN TRANSFORMASIONAL KEPALA MADRASAH TERHADAP PENINGKATAN KINERJA GURU DI MTsS. AS’ADIYAH NO. 2 BONTOUSE KECAMATAN TANASITOLO KABUPATEN WAJO - Sitti Aminah; Hardiyanti Lasmi; Ambo Upe; Muhammad Arafah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study is motivated by the importance of the role of madrasah principals in creating a work environment that supports the improvement of the quality of education in the era of globalization. Transformational leadership is seen as effective because it is able to motivate and empower teachers. Based on initial interviews at MTsS. As'adiyah No. 2 Bontouse, Tanasitolo District, Wajo Regency, there are still obstacles in planning, implementing, and evaluating learning, so further research is needed. The purpose of this study was to determine and analyze the effect of transformational leadership on improving teacher performance. The approach used is a quantitative method with data collection techniques in the form of questionnaires, observation, and documentation. Respondents were 29 teachers, using saturated sampling technique. Data were analyzed using simple linear regression, t test, and determination test. The results showed that the transformational leadership of madrasah principals had a positive and significant effect on improving teacher performance, with a contribution of 39.9%. The remaining 60.1% is influenced by other factors outside the variables studied.